IN A CIVILIZED MANNER-ANTHROPOLOGICAL MEASURING OF GLOBALIZATION - Гейко, С. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article is sanctified to the philosophical-anthropological analysis of globalization that is examined as the integral cultural phenomenon and basic her progress trends are analysed